Allergic contact dermatitis caused by isobornyl acrylate in Freestyle® Libre, a newly introduced glucose sensor - Herman, Anne; Aerts, Olivier; Baeck, Marie; Bruze, Magnus; De Block, Christophe; Goossens, An; Hamnerius, Nils; Huygens, Sara; Maiter, Dominique; Tennstedt, Dominique; Vandeleene, Bernard; Mowitz, Martin (Contact dermatitis, 2017)
SUMMARY Background Glucose sensors, such as FreeStyle® Libre, are innovative medical devices developed for diabetes patients as a replacement for classic glucose meters, ensuring continuous glucose monitoring without the disadvantage of regular skin finger pricks. Objectives To report several cases of allergic contact dermatitis caused by FreeStyle® Libre, and to report on isobornyl acrylate as a culprit allergen. Patients and Methods Fifteen patients presented with allergic contact dermatitis caused by FreeStyle® Libre. All but 1 were patch tested with a baseline series, and with pieces and/or ultrasonic bath extracts of (the adhesive part of) the glucose sensor. Isobornyl acrylate was patch tested, in various concentrations and vehicles, in 13 patients. Gas chromatography–mass spectrometry (GC‐MS) of the sensors was performed. Results All patients reacted to the adhesive part of the sensor, and 12 patients were shown to be sensitized to isobornyl acrylate. Simultaneous reactions to other allergens were rarely observed. GC‐MS showed the presence of isobornyl acrylate in the sensors. Conclusions Cases of allergic contact dermatitis caused by FreeStyle® Libre are increasingly being observed, and isobornyl acrylate is a relevant culprit allergen. Cross‐reactivity to other acrylates was infrequently observed, but other, hitherto unidentified, contact allergens may still be present in the device.